Toll-like receptor 7/8 agonist stimulation rapidly skews the antibody repertoire of B cells in non-human primates - Wang, Shiyu; Citron, Michael; Luo, Lihua; Wang, I-Ming; Liu, Xiao; Zhang, Wei (Frontiers in Immunology, 2025)
IntroductionToll-like receptors 7 and 8(TLR7/8) recognize purine-rich single-stranded RNA from pathogens, triggering immune responses. Although TLR7/8 agonists are emerging as potential novel adjuvants, their impact on the adaptive B cell response, particularly antibody repertoire, remains unclear.MethodsSix Indian rhesus macaques(IRMs) and six African green monkeys(AGMs) were stimulated with a TLR7/8 agonist. Peripheral blood samples were collected pre-stimulation and multiple timepoints within one week post-stimulation for flow cytometry and antibody repertoire sequencing.ResultsB cell activation was observed at 24 hours. Significant increases in antibody repertoire diversity were detected at 48 and 72 hours in both species; however, diversity remained elevated at one week in IRMs but returned to baseline in AGMs. Analysis of antibody lineage distributions revealed a marked increase in increased lineages at 48 and 72 hours, characterized by higher frequency, a greater number of antibody clonotypes, and increased mutation rates. The identified expanded lineages, induced by the TLR7/8 agonist, exhibited λ chain bias and divergent antibodies across individuals, and primarily originated from highly mutated antibodies, likely corresponding to memory/effector-like B cells.ConclusionsOur findings demonstrate that the TLR7/8 agonist rapidly induces a divergent expansion of B cells, establishing an immune foundation supporting vaccine responses and offering new insights into the dynamic B cell modulation.